2015
DOI: 10.1186/s12931-015-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cardiac and peripheral hemodynamic responses to inhaled β2-agonist in cystic fibrosis

Abstract: BackgroundPulmonary system dysfunction is a hallmark of cystic fibrosis (CF) disease. In addition to impaired cystic fibrosis transmembrane conductance regulator protein, dysfunctional β2-adrenergic receptors (β2AR) contribute to low airway function in CF. Recent observations suggest CF may also be associated with impaired cardiac function that is demonstrated by attenuated cardiac output (Q), stroke volume (SV), and cardiac power (CP) at both rest and during exercise. However, β2AR regulation of cardiac and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…For example, whereas observations of Hull et al [20] (ergometry) or Schrage et al [35] (handgrip) do not suggest overt exacerbation of blood pressure during exercise in mild- to- moderate severity adult CF, it is both novel and relevant in understanding peripheral hemodynamic function in CF that Hull et al [20] demonstrated increased augmentation index in these individuals, suggesting the presence of increased arterial stiffness. Further, and consistent with Hull et al [20, 36], our group has demonstrated that mild- to- moderate severity adult CF have blunted reductions in resting systemic vascular resistance in response to inhalation of the β 2 -selective agonist albuterol [19]. Thus, if increased blood pressure, underpinned by impaired peripheral vascular function [1921, 24, 35, 36], does indeed parallel exaggerated slope during exercise in adult CF, demonstrating this calibration in the laboratory setting should help add to our understanding that the clinical implications of CF may extend to the entire cardiovascular system.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…For example, whereas observations of Hull et al [20] (ergometry) or Schrage et al [35] (handgrip) do not suggest overt exacerbation of blood pressure during exercise in mild- to- moderate severity adult CF, it is both novel and relevant in understanding peripheral hemodynamic function in CF that Hull et al [20] demonstrated increased augmentation index in these individuals, suggesting the presence of increased arterial stiffness. Further, and consistent with Hull et al [20, 36], our group has demonstrated that mild- to- moderate severity adult CF have blunted reductions in resting systemic vascular resistance in response to inhalation of the β 2 -selective agonist albuterol [19]. Thus, if increased blood pressure, underpinned by impaired peripheral vascular function [1921, 24, 35, 36], does indeed parallel exaggerated slope during exercise in adult CF, demonstrating this calibration in the laboratory setting should help add to our understanding that the clinical implications of CF may extend to the entire cardiovascular system.…”
Section: Introductionsupporting
confidence: 80%
“…Further, and consistent with Hull et al [20, 36], our group has demonstrated that mild- to- moderate severity adult CF have blunted reductions in resting systemic vascular resistance in response to inhalation of the β 2 -selective agonist albuterol [19]. Thus, if increased blood pressure, underpinned by impaired peripheral vascular function [1921, 24, 35, 36], does indeed parallel exaggerated slope during exercise in adult CF, demonstrating this calibration in the laboratory setting should help add to our understanding that the clinical implications of CF may extend to the entire cardiovascular system.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Patients with CF were instructed to adhere to the timing of their daily treatments and come to the laboratory following their morning airway clearance technique and inhaled medicines. It is worth noting that the use of inhaled ␤-agonists as part of routine treatment of CF does not affect cardiac or peripheral hemodynamics in these patients (52). Microvascular function was assessed; then a pulmonary function test was performed and a blood sample was collected for assessment of standard laboratory values.…”
Section: Experimental Designmentioning
confidence: 99%